Archeologija Vilniaus universitete - Luchtanas, Aleksiejus (Archaeologia Lituana, 1999)
Several stages distinctly stand out in Lithuania in the development of University-level archaeological study. The first stage was in 1919–1940 with the first efforts to teach and prepare specialists. The second stage occurred in 1944–1990 during the period of soviet occupation, when the Archaeology department was opened with limited breakes and specialists were trained. The third stage began in 1990, when the Archaeology department was rehabilitated, a systematic preparation of archaeologists was begun, and a separate speciality formed.